A Facile Way of Enhancing Thermally and Electrically Conductive Properties of Epoxy/Ni/GNP Composites via Construction of a Hybrid Filler Network with a Magnetic Field Orientation Technique. Issue 9 (2nd June 2022) - Yang, Bin; Jia, Ning; Wang, Xiaohong; Pan, Yang; Luo, Mengning; Chen, Xinya; Xia, Ru; Zheng, Zhengzhi; Qian, Jiasheng; Ke, Yuchao; Su, Lifen; Fang, Yirong
Abstract: In this work, epoxy (EP) resin composites with "point‐surface" heterostructures constructed by hybrid fillers of Ni particles and graphene nanosheets (GNPs) are prepared via a blending method under magnetic field. Effects of filler content and magnetic orientation on dielectric, thermally and electrically conductive, and thermomechanical properties of the resultant composites are investigated. The findings disclose that the synergistic effect of hybrid fillers and the magnetic orientation result in the formation of a complex heterogeneous network structure, significantly improving both thermal and electrical conductivities. From the temperature distribution analysis, it is the construction of the heterogeneous network that improves the thermally conductive and thermomechanical properties. Sample Y4 (containing 28 wt% Ni and 2 wt% GNP) displays an average heating rate (AHR) of 152.4 °C min −1 and has an out‐of‐plane thermal conductivity of 0.930 W m −1  K −1 (267.6% higher than that of neat EP). The infrared thermal imaging (ITI) together with SEM observations further confirms that the Ni chains in situ formed under a magnetic field are responsible for the improved composite's thermal conductivity and thermal management capability, which make it potentially applicable for 3D packaging materials in power‐intensive electronic components. Abstract : Magnetic field is aided in constructing the heterogeneous network via the synergistic effect of graphene nanosheets (GNPs) and Ni particles, and enhancement in both thermal and electrical conductivities is achieved with increasing GNPs content. Among all samples, Y4 displays a maximum average heating rate of 152.4 °C min −1, with an out‐of‐plane thermal conductivity of 0.930 W m −1  K −1 .